Exploring the potential activity spectrum of two 5-nitroindazolinone prototypes on different Trypanosoma cruzi strains. (20th November 2015) - FONSECA-BERZAL, CRISTINA; DA SILVA, PATRICIA BERNARDINO; DA SILVA, CRISTIANE FRANÇA; VASCONCELOS, MARIANE; BATISTA, MARCOS MEUSER; ESCARIO, JOSÉ A.; ARÁN, VICENTE J.; GÓMEZ-BARRIO, ALICIA; SOEIRO, MARIA DE NAZARÉ C.
SUMMARY: In the present study, the potential activity of two 5-nitroindazole derivatives previously proposed as suitable antichagasic prototypes was further evaluated on diverse Trypanosoma cruzi strains belonging to two discrete typing units (DTUs) frequently associated with human infection (i.e. DTUs TcII and TcVI). The trypanocidal profile that both 2-benzyl-1-propyl (22) and 2-benzyl-1-butyl (24) derivatives achieved on Tulahuen amastigotes (IC50 = 3·56 ± 0·99 and 6·31 ± 1·04 µ m, respectively) correlates with that of formerly obtained on CL Brener, corroborating an outstanding activity on DTU TcVI parasites. Moreover, a sequential screening on extracellular and intracellular stages of T. cruzi Y (DTU TcII) demonstrated also the effectiveness of 22 and 24 over this strain on a similar range of activity (IC50 epimastigotes = 3·55 ± 0·47 and 7·92 ± 1·63 µ m, IC50 amastigotes = 2·80 ± 0·46 and 9·02 ± 5·26 µ m, respectively). These results, supported by a lack of toxicity registered over either L929 fibroblasts or primary cultures of cardiomyocytes, confirm that 5-nitroindazolinones 22 and 24 display great selectivity on both drug-sensitive (CL and Tulahuen) and drug-moderately resistant (Y) T. cruzi strains, and therefore, represent an important outcome in the research of Chagas disease chemotherapy.